You before me: How vertical collectivism and feelings of threat predicted more socially desirable behaviour during COVID-19 pandemic - Čavojová, Vladimíra; Adamus, Magdalena; Ballová Mikušková, Eva (Current psychology (New Brunswick, N.J.), 2022)
The present study investigated the relationship between outward orientation and COVID-related prosocial behavior, including adherence to containment measures, caring for others and providing support, limiting one's social life and responsible purchasing behavior. A sample of 500 Slovaks (250 women) aged between 18 and 86 (M = 44.32, SD = 15.66) participated in the study and responded to questions concerning their sociodemographic and personality characteristics, collectivism and individualism, the consciousness of future consequences and emotional responses to the pandemic. The results show that apart from the perceived threat of COVID-19, vertical collectivism is among the strongest antecedents of COVID-related prosocial behavior. Specifically, feelings of threat, vertical collectivism, conscientiousness, agreeableness, liberalism, and education predicted more prosocial behavior during the pandemic. Consequently, the study indicates that while excessive fear may have adverse effects on individuals' well-being, appealing to and cultivating collectivistic sentiments could contribute not only to containing the pandemic but also to making others' lives more bearable while it lasts.
Keywords: Future orientation; Big five; COVID-19; Helplessness; Collectivism; Threat